Liposome as carrier therapy for Alzheimer’s disease - Anggraeni, Andi Sri Dewi; Arsita, Emilia Vivi; Suwarman, Adika; Mustofa (Indonesian Journal of Pharmacology and Therapy, 2022)
Alzheimer's disease (AD) is the most common type of dementia. Approximately 50 million people suffer from Alzheimer's and it is expected to increase more than 100 million by 2050. According to the Diagnostic and Statistical Manual of Mental Disorders V (DSM-V), the diagnosis of AD has an onset of memory impairment and cognitive decline. Effective treatment of AD is a major challenge in the field of pharmacy and science due to the restriction from blood brain barrier (BBB). This causes poor access to pills or oral administration. Liposome as a part of nanoparticle showed to be a potential AD treatment because of its biocompatibility, flexibility, and capability to carry various therapeutic molecules across the BBB and into brain cells. Several types of liposomes provide varied therapy effect. Some factors which determine liposomes effectiveness are its structure, mechanism of action; formed; and delivery, and its preparation method. This article reviewed liposomes characteristics which has potency as carrier therapy for AD.